2021
DOI: 10.1007/s10639-021-10467-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Current trends in the digital transformation of higher education institutions in Russia

Abstract: This research aimed to analyze the current trends in the digital transformation of educational institutions. The investigation lasted from November 2019 to May 2020 and was based on three higher educational institutions (HEIs) in the Russian Federation: Belgorod State University, Moscow State Institute of International Relations, and Kutafin Moscow State Law University. The number of respondents enrolled was 420 people. In an attempt to bring together views and experiences of different actors of the educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
0
43
0
2
Order By: Relevance
“…oreover, another implication of the technological advancements to the teaching and learning processes, as described in this study, will be to look into more pertinent teaching methods or platforms (be it in-person or virtual), along with development of (digital) teaching-learning skills for the stakeholders, to fully benefit from the technology-mediated education and process innovations (Almaiah et al, 2020;Mikheev et al, 2021;Mohan et al, 2020;Mpungose, 2020a;Raffaghelli et al, 2020). This means, alongside provision of the various promising learning platforms and programs, that HEIs must also focus their attention towards the digital literacy levels or training for the stakeholders to flourish in the modern day digital-savvy generation (Mpungose, 2020b;UNESCO 2014), as well as, how to fill the voids that the rapid shift from face-to-face to online learning has left for the stakeholders (Armstrong-Mensah et al, 2020).…”
Section: Implications Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…oreover, another implication of the technological advancements to the teaching and learning processes, as described in this study, will be to look into more pertinent teaching methods or platforms (be it in-person or virtual), along with development of (digital) teaching-learning skills for the stakeholders, to fully benefit from the technology-mediated education and process innovations (Almaiah et al, 2020;Mikheev et al, 2021;Mohan et al, 2020;Mpungose, 2020a;Raffaghelli et al, 2020). This means, alongside provision of the various promising learning platforms and programs, that HEIs must also focus their attention towards the digital literacy levels or training for the stakeholders to flourish in the modern day digital-savvy generation (Mpungose, 2020b;UNESCO 2014), as well as, how to fill the voids that the rapid shift from face-to-face to online learning has left for the stakeholders (Armstrong-Mensah et al, 2020).…”
Section: Implications Of This Studymentioning
confidence: 99%
“…They note that students will suffer a learning loss, and that the effects will not affect students equally, and will influence both the cognitive and non-cognitive skills acquisition, including long-term consequences to short-term ones (Burke, 2020;Oyedotun, 2020). Interestingly, the study (Di Pietro et al, 2020) noted some elements that should be part of any successful strategies by the HEIs in integrating (online and offline) teaching-learning activities, to include; proper virtual learning environments (VLE), to guaranteeing access to internet and digital technologies for learning for the stakeholders, and teachers learning how to adapt their roles to situations in which they can effectively communicate with the students (e.g., to not lose motivation when shifting to the online learning platforms), through improved digital competences and pedagogical approaches (Mikheev et al, 2021;Raffaghelli et al, 2020) that are best suited for online learning and/or blended models such as the HyFlex + Tec model described in this study. To note, while Ma et al (2021) found that teachers' online teaching self-efficacy (TSE) in terms of technology-application for learning (Lin & Wang, 2021) increased during the Covid-19 lockdown.…”
Section: Implications Of This Studymentioning
confidence: 99%
“…When developing the program, we took into account the three basic directions of digitalization that most universities are implementing: the development of distance education, the improvement of information infrastructure, digitalization and optimization of business processes [1], [2], [7], [8]. A.V.…”
Section: Directions Of Nefu Development Programmentioning
confidence: 99%
“…At the same time, the studies of digitalization processes in leading Russian universities show that the gap between the digital future and the existing digital competencies of the education system is a significant problem [1]. Modern researchers indicate the following major challenges of education digitalization: lack of experience in setting priorities, insufficient personnel with the necessary competencies, limited resources, and decision-making lagging behind the requirements of modern time [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation